An Overview On The Growth and Development Of The Malaysian Construction Industry - Abdulllah, Fadhlin (2004)
The Malaysian economy enjoyed a period of sustained economic growth up until the mid-1997 East Asian economic crisis. As a result of the government's economic recovery measures, official government statistics estimate that by the end of 2004 GDP growth will increase by 8%. Malaysia's high level of economic growth and the aspiration of becoming a developed and industrialized nation has created the environment for growth, and stimulated changes in construction industry. This paper overviews how the Malaysian construction industry responded to the country's rapid economic development. The paper focuses on Malaysia's rapid economic development and the impact on the growth and changes in construction output. This provides an understanding of the past and present scenario of the construction industry in the economy